Generative Literature: The Role of Artificial Intelligence in the Creative Writing Process - Prabowo, Bayu Ade; Asmarani, Rahmanti (Universitas PGRI Semarang, 2025)
This study explores the emerging phenomenon of AI-generated literature and its implications for creative writing, focusing on the characteristics of AI-generated texts, the impact of AI-human collaboration on the creative process, and the challenges posed by these technologies for traditional concepts of authorship, originality, and creativity. Through a comparative analysis of selected AI-generated literary works and a case study of the